Knowledge transfer of advances in applied health and science - Macnab, Andrew John (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Abstract is not required for this Editorial. Below are the summary and keywords the journal provides for insight to our reader. DOI: https://doi.org/10.35898/ghmj-22202 Summary: The editorial highlighted the practice of starting Global Health Management Journal's edition with selected papers from the prestigious International Conference on Applied Science and Health. The journal follows a gold standard for the peer-review process, ensuring the publication of high-quality research. The primary goal of the journal is to facilitate knowledge transfer and dissemination of advances in applied health and science. The editorial also provides a succinct summary of the key research findings from the selected papers presented at the conference. This approach not only reinforces the journal's dedication to academic rigor but also serves as a platform for sharing valuable insights and advancements in the field of applied health and science. Accepted: 27 June 2018. Keywords: Global Health Management Journal International Conference on Applied Science and Health Gold Standard Peer Review Knowledge Transfer Advances in Applied Health and Science.